Electrolyte composition, electrolyte membrane, and preparation method and application thereof
By using electrolyte compositions of solid electrolytes, lithium salts and TBA-TFSA in solid-state batteries, the problem of poor contact of electrolyte particles in solid-state batteries is solved, and the ion conductivity and crack resistance of the battery are significantly improved, and the service life of the battery is extended and the safety is improved.
Patent Information
- Application Number
- CN202411882077.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
It is difficult to achieve close contact between solid electrolyte particles in solid-state batteries, resulting in poor ion conductivity and insufficient mechanical properties, affecting the cycle stability and service life of the battery.
An electrolyte composition is adopted, including solid electrolyte, lithium salt and tetrabutylbistrifluoromethanesulfonate (TBA-TFSA) as the molten salt, and the ion conductivity and crack resistance of the electrolyte membrane are improved by reasonably optimizing the mass ratio of lithium salt to TBA-TFSA.
It significantly improves the ion conductivity and crack resistance of the electrolyte membrane, improves the cycle stability and service life of the solid-state battery, and improves the safety and endurance of the battery.
Smart Images

Figure BDA0005198440180000091 
Figure BDA0005198440180000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to an electrolyte composition, an electrolyte membrane, and a preparation method and application thereof. Background Art
[0002] As the next generation of lithium battery technology, solid-state batteries inherit the advantages of traditional secondary batteries and have outstanding advantages such as good safety and high energy density. Developing high-energy-density solid-state batteries to replace traditional secondary batteries with liquid electrolyte systems is expected to improve safety in use.
[0003] However, solid electrolyte is a solid-phase material. It is difficult to achieve close contact between solid electrolyte particles. The wettability between particles is poor. Isostatic pressing is usually used to promote interface fusion and increase the contact area between solid electrolyte particles. However, the electrolyte membrane treated with high pressure has poor mechanical properties and is prone to defects such as breakage and cracks. These defects will cause the ion conduction path to be cut off, directly affecting the overall performance of the battery. At the same time, the frequent changes in volume during the solid-solid battery cycle will aggravate the failure of solid-solid point contact, destroy the interface state, and cause capacity decay, resulting in unsatisfactory performance of the solid-state battery, and even causing the solid-state battery itself to be unable to be used normally.
[0004] Therefore, there is still a need to develop a higher performance solid electrolyte material. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides an electrolyte composition, which can significantly improve the ion conductivity and crack resistance of an electrolyte membrane prepared using the electrolyte composition, and help improve the cycle stability and service life of a solid-state battery.
[0006] The invention also provides an electrolyte membrane.
[0007] The present invention also provides a method for preparing the electrolyte membrane.
[0008] The invention also provides a solid-state battery.
[0009] The invention also provides an electric device.
[0010] Specifically, the first aspect of the present invention relates to an electrolyte composition, comprising the following components: a solid electrolyte, a lithium salt and a molten salt; wherein the molten salt is selected from tetrabutylammonium bistrifluoromethanesulfonate, and the mass ratio of the molten salt to the lithium salt is less than or equal to 1:1.
[0011] The electrolyte composition according to the first aspect of the present invention has at least the following beneficial effects:
[0012] Solid electrolytes are used to provide stable ion conduction channels and chemical stability over a wide temperature range. Molten salts can be filled at the interface of solid electrolyte particles and coated on the surface of particles to further improve ion conductivity and interface strength. Compared with other molten salts, tetrabutylammonium bistrifluoromethanesulfonate (TBA-TFSA or TBA-TFSI, CAS No.: 210230-40-3) has a lower melting point and good affinity for solid electrolytes. It is easier to penetrate into the pores of the electrolyte membrane, improving ion conductivity. At the same time, TBA-TFSA has good chemical stability, can reduce side reactions, and improve stability. The use of lithium salts and TBA-TFSA is conducive to the formation of a stable solid electrolyte interface layer (SEI) at the interface between the electrode and the electrolyte, optimizing the ion transmission channel, reducing the interface impedance, and improving the interface stability.
[0013] By rationally optimizing the mass ratio of lithium salt to TBA-TFSA, it is helpful to give full play to the advantages of lithium salt in ionic conductivity. If the proportion of lithium salt is too low, it may not provide sufficient ion source, resulting in insufficient ionic conductivity.
[0014] Therefore, the present invention significantly improves the ion conductivity and crack resistance of the electrolyte membrane prepared using the electrolyte composition by reasonably matching the solid electrolyte, TBA-TFSA and lithium salt, which is beneficial to improving the cycle stability and service life of the solid-state battery.
[0015] According to some embodiments of the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide (Li-TFSA or Li-TFSI), lithium bis(fluorosulfonyl)imide, and lithium oxalate.
[0016] According to some embodiments of the present invention, the lithium salt is selected from Li-TFSA. Li-TFSA has high chemical stability and can form a more stable SEI film between the solid electrolyte and the electrode, thereby improving the safety of the battery.
[0017] According to some embodiments of the present invention, the mass ratio of the molten salt to the lithium salt is 0.01 to 0.5:1, and non-limiting examples include: 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1 or any value therebetween. Controlling the ratio of the molten salt to the lithium salt within a certain range helps to balance the advantages of the two. A lower proportion of the molten salt can reduce its adverse effect on ionic conductivity, give full play to the advantages of the lithium salt in ionic conductivity, and facilitate the formation of a more stable SEI film.
[0018] According to some embodiments of the present invention, the mass ratio of the molten salt to the lithium salt is 0.01 to 0.1:1.
[0019] According to some embodiments of the present invention, the total mass of the molten salt and the lithium salt accounts for 1% to 50% of the mass of the electrolyte composition, specifically 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any value therebetween.
[0020] According to some embodiments of the present invention, the solid electrolyte includes at least one of a sulfide solid electrolyte, a halide solid electrolyte, and an oxide solid electrolyte. Among them, the sulfide solid electrolyte has a more excellent ion conductivity, and the halide and oxide solid electrolytes have better stability and are less prone to side reactions. Since the chemical stability of molten salts is high, the use of sulfide solid electrolytes can also ensure stability.
[0021] Specifically, non-limiting examples of sulfide solid electrolytes include: containing, for example, Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, In) and S element, and in addition, may contain halogen elements (at least one of Cl, Br, I) or O element. The sulfide solid electrolyte may be glass-type, glass-ceramic type, or crystalline. Crystalline types, such as Thio-LISICON type crystalline phase, LGPS type crystalline phase, silver-germanite type crystalline phase, etc. In addition, as oxide solid electrolytes and halide solid electrolytes, well-known solid electrolytes can be used. For example, an oxide solid electrolyte contains at least Li and O elements, non-limiting examples: garnet type, perovskite type, etc.; a halide solid electrolyte contains at least Li and halogen elements, non-limiting examples: Li 3 InCl 6 , Li 2 CdCl 4 , Li 2 MgCl 4 , Li 2 ZnI 4 , Li 2 CdI 4 The solid electrolyte can be purchased from the market or prepared by methods known in the art.
[0022] According to some embodiments of the present invention, the electrolyte composition also includes a binder for promoting adhesion between components. The present invention does not specifically limit the type and amount of the binder. The binder can be of a type known in the art, and non-limiting examples include: polyvinylidene fluoride, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polytetrafluoroethylene, cellulose (e.g., carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, methyl hydroxyethyl cellulose, hydroxypropyl cellulose), polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, styrene / ethylene / butylene copolymer (SEBS), hydrogenated SBS, polyamide, polyimide, polyacrylamide and acrylic polymer (e.g., sodium polyacrylate) at least one. The amount of the binder can be determined according to specific needs and experience, for example, it can be selected as 0.1% to 10% of the mass of the electrolyte composition.
[0023] According to some embodiments of the present invention, the mass of the binder accounts for 0.1% to 5% of the mass of the electrolyte composition.
[0024] A second embodiment of the present invention relates to an electrolyte membrane, the raw materials for preparing the electrolyte membrane include the above-mentioned electrolyte composition.
[0025] The electrolyte membrane according to the second aspect of the present invention has at least the following beneficial effects:
[0026] The electrolyte membrane significantly improves the ion conductivity and crack resistance by rationally matching solid electrolyte, TBA-TFSA and lithium salt, optimizes the ion transmission channel, reduces the interface impedance, and can improve the cycle stability and service life of the solid-state battery prepared using the electrolyte membrane.
[0027] According to some embodiments of the present invention, the thickness of the electrolyte membrane is 15 to 100 μm, for example, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm or any value therebetween. The present invention has no strict requirements on the thickness of the electrolyte membrane, and can be reasonably selected according to specific application requirements.
[0028] A third aspect of the present invention relates to a method for preparing the electrolyte membrane, comprising: mixing components including the solid electrolyte, lithium salt and molten salt with a solvent to prepare a slurry, and coating and drying the obtained slurry to obtain the electrolyte membrane.
[0029] The method for preparing an electrolyte membrane according to the third aspect of the present invention has at least the following beneficial effects:
[0030] During the slurrying process, the solvent can dissolve the lithium salt and the molten salt (and can also dissolve the binder when the binder is included) to achieve uniform mixing. The solid electrolyte is difficult to dissolve, so a slurry is formed with the solid electrolyte as the dispersed phase and the solution containing the lithium salt and the molten salt as the continuous phase. The lithium salt and the molten salt can be wrapped around the solid electrolyte, fill the internal gap of the solid electrolyte after drying, and coat the surface of the solid electrolyte, effectively improving the ion conduction characteristics and crack resistance of the electrolyte membrane.
[0031] According to some embodiments of the present invention, the slurry is coated on a surface of a substrate, and after drying, the substrate is peeled off to obtain the electrolyte membrane.
[0032] According to some embodiments of the present invention, the substrate is a metal foil or a release film, such as aluminum foil, copper foil, PET film, etc. The present invention has no strict restrictions on the thickness of the substrate, and a common thickness type can be selected according to actual application requirements.
[0033] According to some embodiments of the present invention, the solvent is selected from at least one of alcohols, ethers, esters, ketones, nitriles, amides, sulfones, and sulfoxides. The present invention has no particular limitation on the specific type of solvent, which may be a single solvent or a mixture of two or more solvents.
[0034] Among them, non-limiting examples of alcohol solvents include: methanol, ethanol, n-propanol, isopropanol, butanol, benzyl alcohol, propylene glycol, butanediol, triethylene glycol, hexylene glycol, ethoxylated diethylene glycol or dipropylene glycol.
[0035] Non-limiting examples of ether solvents include: ethyl ether, dimethyl ether, diethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, dioxolane, dioxane, 4-methyldioxolane or anisole. It should be noted that alcohol ether solvents (such as methyl glycol ether, ethyl glycol ether or isopropyl glycol ether) can also be classified as alcohol or ether solvents.
[0036] Non-limiting examples of ester solvents include triglycerides, ethyl acetate, butyl acetate, isobutyl isobutyrate, γ-butyrolactone, diethylene glycol ether acetate, or methoxypropyl acetate.
[0037] Non-limiting examples of ketone solvents include: acetone, methyl ethyl ketone, or methyl isobutyl ketone.
[0038] Non-limiting examples of nitrile solvents include acetonitrile, propionitrile, butyronitrile, succinonitrile or benzonitrile.
[0039] Non-limiting examples of amide solvents include: N,N-dimethylformamide, N,N-dimethylacetamide, fatty acid amides or N-alkylpyrrolidone.
[0040] Non-limiting examples of sulfone or sulfoxide solvents include sulfolane or dimethyl sulfoxide.
[0041] Any one of the above solvents can be selected according to specific needs, or a combination of any two or more solvents can be selected. In addition, other solvents known in the art that can dissolve lithium salts and molten salts can also be used.
[0042] According to some embodiments of the present invention, the solid content of the slurry is 35% to 60%, for example, specifically 35%, 40%, 45%, 50%, 55%, 60% or any value therebetween. The solid content of the slurry is the mass fraction of other components (such as the electrolyte composition) except the solvent. The present invention has no strict restrictions on the solid content of the slurry, and can be adjusted according to actual needs and experience.
[0043] According to some embodiments of the present invention, the electrolyte composition is mixed with a solvent to prepare pulp, and the specific method is: all components of the electrolyte composition (including solid electrolyte, lithium salt and molten salt, and further including a binder) are mixed with a solvent to prepare pulp in one step; or the lithium salt and the molten salt are first compounded, and then mixed with the remaining components and the solvent to prepare pulp. Since lithium salt and molten salt have good solubility, are easy to dissolve and evenly disperse, the one-step pulping method can simplify the process and improve production efficiency.
[0044] According to some embodiments of the present invention, the coating is performed by blade coating or casting process.
[0045] According to some embodiments of the present invention, the drying temperature is 40-80° C. For example, it can be 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C. or any value therebetween.
[0046] According to some embodiments of the present invention, the drying time is 2 to 24 hours. For example, it can be 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours or any value therebetween.
[0047] By controlling the drying temperature and time, the side reactions can be reduced while ensuring the drying rate.
[0048] According to some embodiments of the present invention, the slurrying includes stirring or grinding. There is no specific requirement for the process parameters such as the stirring or grinding speed. As an example, the stirring or grinding speed can be selected as 300 to 10000 rpm, and the processing time can be selected as 1 to 10 minutes. When the solid electrolyte needs to be refined, a grinding process can be selected for slurrying.
[0049] According to some embodiments of the present invention, the slurrying and / or drying is performed at an ambient dew point temperature of less than -50°C (standard atmospheric pressure), thereby reducing the impact of ambient moisture and improving the long-term stability of the solid electrolyte.
[0050] According to some embodiments of the present invention, the slurrying and / or drying is performed under an inert atmosphere (eg, nitrogen).
[0051] A fourth aspect of the present invention provides a solid-state battery, comprising a positive electrode sheet, a negative electrode sheet and the above-mentioned electrolyte membrane.
[0052] Solid-state batteries, due to the use of the above electrolyte membrane, can effectively reduce the interface internal resistance by virtue of the advantages of the electrolyte membrane in ion conductivity and crack resistance, so that the battery can maintain higher stability and longer service life during the charging and discharging process, and improve the safety of use. The battery can be prepared by conventional methods and is suitable for large-scale industrial production.
[0053] A fifth aspect of the present invention provides an electrical device comprising the above-mentioned solid-state battery.
[0054] The electrical device adopts the above solid-state battery, which significantly improves the safety and service life of the electrical device due to its advantages in ion conductivity and stability. By enhancing ion conductivity and interface strength, it can better cope with high-load working environment, extend the service life of the battery, improve its stability under long-term operation conditions, and improve endurance.
[0055] According to some embodiments of the present invention, the power-consuming device includes electric vehicles (such as hybrid electric vehicles, pure electric vehicles, extended-range electric vehicles, electric engineering vehicles, electric motorcycles, electric bicycles, etc.), energy storage devices (such as household energy storage systems, photovoltaic energy storage systems), mobile devices (such as smart phones, tablet computers, laptops, etc.), etc. Using the solid-state battery as a power source can provide more durable and efficient energy output, which not only extends the cruising range of the device, but also improves the safety of long-term use.
[0056] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0057] Embodiments of the present invention are described in detail below. The embodiments are exemplary and are only used to explain the present invention, but are not to be construed as limiting the present invention.
[0058] In the following examples and comparative examples, some raw materials are described as follows:
[0059] Sulfide solid electrolyte: Li6 PS 5 Cl(LPSC).
[0060] Halide solid electrolyte: Li 3 InCl 6 (lithium indium chloride, LIC).
[0061] Non-woven fabric: PET, thickness 15 μm, average pore size 5 μm, porosity 80%.
[0062] Unless otherwise specified, all raw materials and equipment used are commercially available conventional products.
[0063] Example 1
[0064] This embodiment prepares an electrolyte membrane, including the following preparation steps:
[0065] S1: Weigh the sulfide solid electrolyte, TBA-TFSA, Li-TFSA and SEBS binder, wherein the mass ratio of TBA-TFSA to Li-TFSA is 0.05:1, the total mass fraction of TFSA and Li-TFSA is 1%, and the mass fraction of SEBS binder is 2%. Put the above raw materials into isobutyl isobutyrate solvent, stir and mix with a stirrer, control the ambient dew point temperature to be less than -50°C (under standard atmospheric pressure), and stir at a constant speed of 1400rpm for 1 minute to obtain a slurry (solid content 40%).
[0066] S2: Coat the above slurry on aluminum foil and dry it in an oven at 60°C for 24 hours. During the drying process, keep the dew point temperature of the environment less than -50°C, or fill the environment with nitrogen for protection. After drying, peel off the aluminum foil to obtain an electrolyte membrane with a dry film thickness of 30μm.
[0067] Example 2
[0068] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 4%, and the other preparation methods and conditions are the same as those in embodiment 1.
[0069] Example 3
[0070] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 6%, and the other preparation methods and conditions are the same as those in embodiment 1.
[0071] Example 4
[0072] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 8%, and the other preparation methods and conditions are the same as those in embodiment 1.
[0073] Example 5
[0074] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 10%, and the other preparation methods and conditions are the same as those in embodiment 1.
[0075] Example 6
[0076] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 20%, and the other preparation methods and conditions are the same as those in embodiment 1.
[0077] Example 7
[0078] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 30%, and the other preparation methods and conditions are the same as those in embodiment 1.
[0079] Example 8
[0080] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 40%, and the other preparation methods and conditions are the same as those in embodiment 1.
[0081] Example 9
[0082] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 50%, and the other preparation methods and conditions are the same as those in embodiment 1.
[0083] Example 10
[0084] S1: Weigh the halide solid electrolyte, TBA-TFSA, Li-TFSA and SEBS binder, wherein the mass ratio of TBA-TFSA to Li-TFSA is 0.05:1, the total mass fraction of TFSA and Li-TFSA is 1%, and the mass fraction of SEBS binder is 2%. Put the above raw materials into isobutyl isobutyrate solvent, stir and mix with a stirrer, control the ambient dew point temperature to be less than -50°C (under standard atmospheric pressure), and stir at a constant speed of 1400rpm for 1 minute to obtain a slurry (solid content 40%).
[0085] S2: Coat the above slurry on aluminum foil and dry it in an oven at 60°C for 24 hours. During the drying process, keep the dew point temperature of the environment less than -50°C, or fill the environment with nitrogen for protection. After drying, peel off the aluminum foil to obtain an electrolyte membrane with a dry film thickness of 30μm.
[0086] Embodiment 11
[0087] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 4%, and the other preparation methods and conditions are the same as those of embodiment 10.
[0088] Example 12
[0089] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 6%, and the other preparation methods and conditions are the same as those of embodiment 10.
[0090] Embodiment 13
[0091] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 8%, and the other preparation methods and conditions are the same as those of embodiment 10.
[0092] Embodiment 14
[0093] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 10%, and the other preparation methods and conditions are the same as those of embodiment 10.
[0094] Embodiment 15
[0095] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 20%, and the other preparation methods and conditions are the same as those of embodiment 10.
[0096] Example 16
[0097] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 30%, and the other preparation methods and conditions are the same as those of embodiment 10.
[0098] Embodiment 17
[0099] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 40%, and the other preparation methods and conditions are the same as those of embodiment 10.
[0100] Embodiment 18
[0101] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 50%, and the other preparation methods and conditions are the same as those of embodiment 10.
[0102] Comparative Example 1
[0103] S1: Weigh the sulfide solid electrolyte and SEBS binder, wherein the mass fraction of SEBS binder is 2%. Put the above raw materials into isobutyl isobutyrate solvent, stir and mix with a stirrer, control the ambient dew point temperature to be less than -50°C (under standard atmospheric pressure), and stir at a constant speed of 1400 rpm for 1 minute to obtain a slurry (solid content 40%).
[0104] S2: Coat the above slurry on an aluminum foil current collector and dry it in an oven at 60°C for 24 hours. During the drying process, keep the dew point temperature of the environment below -50°C, or fill the environment with nitrogen for protection. Peel off the aluminum foil to obtain an electrolyte membrane with a dry film thickness of 30 μm.
[0105] Comparative Example 2
[0106] S1: Weigh the halide solid electrolyte and SEBS binder, wherein the mass fraction of SEBS binder is 2%. Put the above raw materials into isobutyl isobutyrate solvent, stir and mix with a stirrer, control the ambient dew point temperature to be less than -50°C (under standard atmospheric pressure), and stir at a constant speed of 1400 rpm for 1 minute to obtain a slurry (solid content 40%).
[0107] S2: Coat the above slurry on an aluminum foil current collector and dry it in an oven at 60°C for 24 hours. During the drying process, keep the dew point temperature of the environment below -50°C, or fill the environment with nitrogen for protection. Peel off the aluminum foil to obtain an electrolyte membrane with a dry film thickness of 30 μm.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 1 is that the mass ratio of TBA-TFSA to Li-TFSA is 1:0.5, and step S2 is different. Other preparation methods and conditions are the same as those in Example 1.
[0110] S2: The slurry obtained in step S1 is evenly coated on the upper and lower surfaces of the non-woven fabric, and dried in an oven at 60°C for 24 hours. During the drying process, the dew point temperature of the environment is kept below -50°C, or nitrogen is filled into the environment for protection to obtain a composite solid electrolyte membrane with a dry film thickness of 30 μm.
[0111] Comparative Example 4
[0112] The difference between this comparative example and Example 1 is that the mass of Li-TFSA is 0, the mass fraction of TBA-TFSA is 1%, and step S2 is different. Other preparation methods and conditions are the same as those in Example 1.
[0113] S2: The slurry obtained in step S1 is evenly coated on the upper and lower surfaces of the non-woven fabric, and dried in an oven at 60°C for 24 hours. During the drying process, the dew point temperature of the environment is kept below -50°C, or nitrogen is filled into the environment for protection to obtain a composite solid electrolyte membrane with a dry film thickness of 30 μm.
[0114] Comparative Example 5
[0115] The difference between this comparative example and Example 1 is that the molten salt is 1-butyl-3-methylimidazole bis(trifluorosulfonyl)imide (CAS No.: 174899-83-3), the mass ratio of the molten salt to Li-TFSA is 0.05:1, and step S2 is different. The other preparation methods and conditions are the same as those in Example 1.
[0116] S2: The slurry obtained in step S1 is evenly coated on the upper and lower surfaces of the non-woven fabric, and dried in an oven at 60°C for 24 hours. During the drying process, the dew point temperature of the environment is kept below -50°C, or nitrogen is filled into the environment for protection to obtain a composite solid electrolyte membrane with a dry film thickness of 30 μm.
[0117] Test Case
[0118] The ionic conductivity and crack resistance of the electrolyte membranes prepared in the above-mentioned embodiments and comparative examples were tested. The test results are shown in Table 1.
[0119] Among them, the ionic conductivity is tested by an AC impedance tester, and the specific test conditions are: temperature: 25°C, frequency: 0.01~7MHz.
[0120] Cracking resistance: Wrap the electrolyte membrane around a cylinder with a diameter of 1 cm and visually inspect whether cracks occur.
[0121] Table 1
[0122]
[0123]
[0124] From the above results, it can be seen that the combination of solid electrolyte, TBA-TFSA and lithium salt improves the ionic conductivity and crack resistance of the electrolyte membrane.
[0125] Comparison between Example 1 and Example 10 shows that the ionic conductivity of Comparative Example 1 and Comparative Example 2 is significantly lower than that of Example 1 and Example 10, respectively, because TBA-TFSA and lithium salt are not added. In addition, cracking occurs in both Comparative Example 1 and Comparative Example 2, indicating that TBA-TFSA can improve the mechanical properties of the electrolyte membrane, which may be due to the buffering effect provided by its low modulus.
[0126] In Comparative Example 3, the proportion of TBA-TFSA is too high, resulting in a decrease in ionic conductivity; in Comparative Example 4, all lithium salts are replaced with TBA-TFSA, and the ionic conductivity is further reduced. This shows that in order to obtain excellent ionic conductivity, it is necessary to reasonably control the content of TBA-TFSA.
[0127] In Comparative Example 5, other molten salts were used instead of TBA-TFSA, resulting in an ionic conductivity lower than that of Example 1. This may be because TBA-TFSA has better compatibility with other components and can significantly improve the interfacial conductivity.
[0128] It should be noted that although non-woven fabrics are added in Comparative Examples 3-5, studies have shown that non-woven fabrics help to build a wide range of ion conduction networks, so the addition of non-woven fabrics will not have a negative impact on the conductivity of the electrolyte membrane. For example, based on Example 1, if the slurry is coated on the upper and lower surfaces of a non-woven fabric (thickness 15 μm, average pore size 5 μm, porosity 80%) and an electrolyte membrane of the same thickness (30 μm) is made, its conductivity is basically equivalent to that of Example 1. Therefore, the changes in conductivity of Comparative Examples 3-5 mainly reflect the effects of the type and amount of molten salt or lithium salt on conductivity.
[0129] It can be understood that since the ionic conductivity and crack resistance of the electrolyte membrane are improved, the cycle capacity and cycle stability of the battery can be improved, which helps to improve the cruising range and long-term use safety of electrical devices such as electric vehicles.
[0130] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. An electrolyte composition, characterized in that Contains the following ingredients: A solid electrolyte, a lithium salt and a molten salt; wherein the molten salt is selected from tetrabutylammonium bistrifluoromethanesulfonate; and the mass ratio of the molten salt to the lithium salt is less than or equal to 1:
1.
2. The electrolyte composition according to claim 1, characterized in that The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), and lithium oxalate; and / or, the mass ratio of the molten salt to the lithium salt is 0.01 to 0.1:1; and / or, the total mass of the molten salt and the lithium salt accounts for 1% to 50% of the mass of the electrolyte composition.
3. The electrolyte composition according to claim 1, characterized in that The electrolyte composition also includes a binder; Optionally, the mass of the binder accounts for 0.1% to 10% of the mass of the electrolyte composition.
4. The electrolyte composition according to claim 1, characterized in that The solid electrolyte includes at least one of a sulfide solid electrolyte, a halide solid electrolyte, and an oxide solid electrolyte.
5. An electrolyte membrane, characterized in that: The raw material for preparing the electrolyte membrane comprises the electrolyte composition according to any one of claims 1 to 4.
6. The electrolyte membrane according to claim 5, characterized in that The thickness of the electrolyte membrane is 15-100 μm.
7. The method for preparing an electrolyte membrane according to claim 5 or 6, characterized in that: include: The components including the solid electrolyte, lithium salt and molten salt are mixed with a solvent to prepare slurry, and the obtained slurry is coated and dried to obtain the electrolyte membrane.
8. The preparation method according to claim 7, characterized in that: The solvent is selected from at least one of alcohols, ethers, esters, ketones, nitriles, amides, sulfones and sulfoxides; and / or the solid content of the slurry is 35% to 60%; and / or the drying temperature is 40 to 80° C.; and / or the drying time is 2 to 24 hours.
9. A solid-state battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, and the electrolyte membrane as claimed in claim 5 or 6.
10. An electrical device, characterized in that: Comprising the solid-state battery as claimed in claim 9.